2016
DOI: 10.1089/chi.2015.0139
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in Body Fat for Healthy Chinese Children and Adolescents

Abstract: Gender differences in the patterns of proportion and distribution of body fat were found. We present sex-specific percentile curves for Total FM%-age, TrAppFMR-age, and TrLLFMR-age relationships in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
3
14
1
Order By: Relevance
“…TPFR tended, however, to be lower in the Samoan sample than in other populations. Average TPFR in Samoan girls and boys was 0.66 and 0.62, respectively, compared with an average TPFR in girls and boys of 0.83 and 0.85 in a study of 129 Chinese 5‐year‐olds (who are the only ethnicity, to our knowledge, to have published data on this measure in young children) . Our TPFR values did not appreciably change with increasing age, so differences in the age composition of our sample compared with the Chinese study likely do not explain the differences observed.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…TPFR tended, however, to be lower in the Samoan sample than in other populations. Average TPFR in Samoan girls and boys was 0.66 and 0.62, respectively, compared with an average TPFR in girls and boys of 0.83 and 0.85 in a study of 129 Chinese 5‐year‐olds (who are the only ethnicity, to our knowledge, to have published data on this measure in young children) . Our TPFR values did not appreciably change with increasing age, so differences in the age composition of our sample compared with the Chinese study likely do not explain the differences observed.…”
Section: Discussioncontrasting
confidence: 56%
“…Regional percent body fat (%BF) and lean mass (%LM) were therefore calculated by dividing fat mass and lean mass, respectively, by total mass (less head). The trunk‐to‐peripheral fat ratio (TPFR) was calculated by dividing trunk fat by the sum of arm and leg fat to describe relative fat distribution, with a higher TPFR indicating greater fat storage in the trunk relative to the periphery …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FM has also been shown to be a key predictor of BMD and may affect bone via both loading and hormonal mechanisms 4. Ageing is associated with gradual changes in body composition, and these changes may be entirely different between men and women, as well as premenopausal and postmenopausal women 5 6. To further explore the changes in body composition with age is one of the purposes of our study.…”
Section: Introductionmentioning
confidence: 99%
“…performed a systematic molecular-level analysis (mainly including mRNA, DNA methylation, microRNA (miRNA) and protein expression levels), and suggested to develop sex-specific therapeutic strategies in certain cancer types1. Recent studies suggest that proteomes may differ between males and females23, and sex differences may exist in mRNA4, miRNA expression567 and isomiR (miRNA variants) expression levels89. For example, AT2R can influence vascular responses with sexually dimorphic10, and some genes are influenced by androgens or estrogen1112.…”
mentioning
confidence: 99%